การพัฒนาอุปกรณ์ปฏิบัติการบนขั้วไฟฟ้าเพื่อการตรวจวัดตะกั่วและทองแดงพร้อมกันโดยเทคนิคดิฟเฟอเรนเชียลพัลส์แอโนดิกสทริปปิงโวลแทมเมตรี - เสียงเพราะ, วีณา; ย่อมเที่ยงแท้, ภาณุมาศ; รุ่งเรืองภาวรรณ, ชัยธวัช (Science Essence Journal, 2017)
บทคัดย่อ งานวิจัยนี้มุ่งเน้นศึกษาและพัฒนาอุปกรณ์ปฏิบัติการบนขั้วไฟฟ้าเพื่อการตรวจวัดปริมาณตะกั่วและทองแดงพร้อมกันในตัวอย่างน้ำ อุปกรณ์ปฏิบัติการบนขั้วไฟฟ้าประกอบด้วยขั้วไฟฟ้า 3 ชนิด ได้แก่ ขั้วไฟฟ้าคาร์บอนพิมพ์สกรีนดัดแปรด้วยอนุภาคทองนาโนและฟิล์มปรอทเป็นขั้วไฟฟ้าใช้งาน ขั้วไฟฟ้าคาร์บอนและขั้วไฟฟ้าซิลเวอร์/ซิลเวอร์คลอไรด์ เป็นขั้วไฟฟ้าช่วยและขั้วไฟฟ้าอ้างอิง ตามลำดับ การตรวจวัดทำโดยการหยดสารละลายมาตรฐานหรือสารละลายตัวอย่างลงบนอุปกรณ์ปฏิบัติการบนขั้วไฟฟ้า และตรวจวัดโดยเทคนิคดิฟเฟอเรนเชียลพัลส์แอโนดิกสทริปปิงโวลแทมเมตรี สภาวะที่เหมาะสมในการตรวจวัด คือ ใช้สารละลายเกื้อหนุนกรดไฮโดรคลอริกเข้มข้น 0.1 โมลาร์ ใช้ศักย์ไฟฟ้าในการสะสมโลหะ -0.9 โวลต์ ใช้เวลาการสะสมโลหะ 90 วินาที และแอมพลิจูดเท่ากับ 100 มิลลิโวลต์ จากผลการศึกษาพบว่าสามารถวิเคราะห์ปริมาณตะกั่วและทองแดงได้ในช่วงความเข้มข้น 10 -100 ส่วนในพันล้านส่วน (r2 = 0.9919) และในช่วงความเข้มข้น 5-100 ส่วนในพันล้านส่วน (r2 =0.9992) ตามลำดับ ขีดจำกัดต่ำสุดของการวิเคราะห์ตะกั่วและทองแดงที่ได้จากการทดลอง มีค่าเท่ากับ 10 และ 5 ส่วนในพันล้านส่วน ตามลำดับ อุปกรณ์ปฏิบัติการบนขั้วไฟฟ้าถูกนำไปประยุกต์วิเคราะห์หาปริมาณตะกั่วและทองแดงในตัวอย่างน้ำที่ไม่ต้องผ่านกระบวนการบำบัดใดๆ ให้ค่าร้อยละการกลับคืนการตรวจวัดตะกั่วและทองแดงอยู่ในช่วง 98.70-116.32% และ 92.83-114.66% และความเที่ยงอยู่ในช่วง 3.58-5.46% และ 3.08-6.47% ตามลำดับ - - - Development of Lab-on-Electrode for Simultaneous Determination of Lead and Copper by Differential Pulse Anodic Stripping Voltammetry ABSTRACT This research aims to study and develop lab-on-electrode for simultaneous determination of lead (II) and copper (II) in water samples. Lab-on-electrode is composed of three-electrode system including screen-printed carbon electrode modified with gold nanoparticles and mercury film served as working electrode. Carbon electrode and silver/silver chloride were used as counter and reference electrode, respectively. The measurement is performed by dropping standard or sample solution onto lab-on-electrode and signal is recorded by differential pulse anodic stripping voltammetry. The optimal conditions were using electrolyte medium of 0.1 M hydrochloric acid, accumulation potential at -0.9 V, accumulate time of 90 s and amplitude of 100 mV. From the results obtained, the developed assay for lead (II) and copper (II) showed linear over the concentration range from 10-100 ppb (r2= 0.9919) and 5-100 ppb (r2= 0.9992), respectively. The limits of detection obtained from the experiment were 10 ppb for lead (II) and 5 ppb for copper (II), respectively. In addition, lab-on-electrode has been successfully applied to determine lead (II) and copper (II) in real water samples without any special pre-treatment. The recoveries are in the range from 98.70-116.32 %, 92.83-114.66 % and precision (RSD) values ​​ranged from 3.58-5.46% and 3.08-6.47% for lead (II) and copper (II), respectively.